Montreal Cognitive Assessment Hearing Impairment (MoCA-H): cross-cultural adaptation to Brazilian Portuguese - Rochele Martins Machado; Karina Carlesso Pagliarin; Fernanda Soares Aurélio Patatt (CoDAS, 2025)
ABSTRACT Purpose This study aimed to adapt the Montreal Cognitive Assessment Hearing Impaired (MoCA-H) into Brazilian Portuguese (BP). Methods This was a descriptive, cross-sectional, quantitative, and qualitative study involving participants selected by convenience. The instrument was adapted from its original version, in a six-stage process consisting of the following: Stage 1 - Translation and back translation of the MoCA-H; Stage 2 - Stimulus analysis and selection; Stage 3 - Semantic analysis of stimuli; Stage 4 - Analysis by non-expert judges, part 1; Stage 5 - Analysis by non-expert judges, part 2; Stage 6 - Pilot study. The following statistical methods were used in this study: parametric T-test, Gwet’s first-order Agreement Coefficient (AC1), and the Content Validity Ratio (CVR). Results Cultural and linguistic adaptations were made to the instrument as well as changes to administration procedures to improve respondent comprehension. Participants with and without hearing loss had some comprehension difficulties in the visualspatial/executive domain task. This was observed not only in Stage 6 but also from the beginning of the adaptation process. Conclusion The adaptation process yielded an instrument with satisfactory content validity.